Predictors of successful percutaneous coronary intervention in chronic total coronary occlusions - Baykan, Ahmet Oytun; Gür, Mustafa; Acele, Armağan; Şeker, Taner; Quisi, Alaa; Kıvrak, Ali; Yıldırım, Arafat; Uçar, Hakan; Akyol, Selahattin; Çaylı, Murat (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction : Percutaneous coronary intervention (PCI) of chronic total coronary occlusions (CTOs) is one of the most challenging procedures of interventional cardiology and is associated with increased risk of significant complications. However, debate continues in regard to which factors adversely influence the success rate of PCI and whether the benefits of revascularization of CTO outweigh the risks and challenges. Aim : To analyze the relationship between lesion characteristics and overall success rates as well as in-hospital outcomes after PCI for CTO. Material and methods : We retrospectively examined the procedural outcomes of 173 consecutive native coronary artery CTO PCIs performed from February 2012 to March 2013 (78% men; mean age: 60.3 ±12.1 years). Results : The CTO target vessel was the right coronary artery (53.8%), circumflex (10.4%) and left anterior descending artery (35.8%), respectively. The retrograde approach was used in 13.9% of all procedures. Successful revascularization was achieved in 83.2% of patients. Major complications occurred in 13.3% of patients. In multivariate analysis, bridge collaterals, severe calcification and tortuosity as well as tandem occlusions were independent predictors of procedural failure, whereas existence of micro-channels was the only predictor of procedural success. Conclusions : Revascularization of coronary CTOs may be performed with high success and low major complication rates. Bridge collaterals, severe calcification and tortuosity, tandem/multiple occlusions and micro-channels were independent predictors of successful CTO revascularization.